Social Identity and Class Climate in the Information Literacy Classroom: Cultivating Intellectual Empathy and Critical Reflection - Baer, Andrea (Université d'Ottawa | University of Ottawa, 2018)
This paper explores scholarship on class climate and social identity and its implications for information literacy education. This literature suggests ways to help students engage in critical thinking, reflection, and dialogue and to consider issues from varying perspectives. These abilities are essential to being an engaged and empathetic world citizen.